Gamifying academic research of near extinct moribund words to preserve culture and heritage - Sheik Said, Normahdiah; Suboh, Nadia (2014)
Net- Gens of today are faced with a dilemma of defining their boundaries in professionalism, livelihood, self-efficacy, social wellbeing, and the appreciation of cultural and heritage in this borderless world through the presence of immersive technologies. New demands of immersiveness in technologies are enabling them not only knowing more about the world beyond the four walls to their home, but also in giving them the chance to get direct access to information, individuals, institutes and organizations playing roles as researchers, clients, informants, participants, communities, and professionals across disciplines, across societies and across nations. This present era and trends has made us rethink about the way we look at deliverables of academic research findings today. A useful approach in answering part of the question on “Is the shift to commercialization in academic research affecting the standards of quality to serve the society?” is to look at a case sample and question the possibilities and constraints the case upholds in justifying or contradicting the said statement. This paper will look at how findings from an academic language research, that in previous forms of deliverables, are as presented papers on selected academic disciplines of conferences and seminars, as online reference journals, or as printed on the shelve hard copy journals in physical knowledge management buildings like archives, resource centers and libraries could be transformed into a present deliverables much more appealing to the Net-Gens of today. The paper will describe how a gamification approach was used and discussed whether such an effort could be a current approach of academic research findings deliverables that could serve still good quality standards to the society towards the shift to commercialization. The chosen game like gamified form “RICEVILLE” case sample was developed from an academic research finding in the context of exploring a new effort to uplift the preservation and appreciation culture and heritage.